Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.juro.2006.09.036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ischemia Time During Open Nephron Sparing Surgery on Solitary Kidneys: A Multi-Institutional Study

Abstract: Vascular clamping during open nephron sparing surgery is associated with a higher incidence of renal complications. Attempts to limit warm ischemia to 20 minutes and cold ischemia to 35 minutes should be used when vascular clamping is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(175 citation statements)
references
References 20 publications
9
148
1
13
Order By: Relevance
“…Diagnostic equipment technologic development has been providing new findings of ever smaller renal tumors in young individuals, therefore making way to needs of nephron sparing during surgical procedures towards removing such tumors; and partial nephrectomy relates to renal ischemia in order to allow nodule or renal mass removals; and, in order to prevent acute tubular necrosis, damage reduction due to blockage of renal blood flow -one of its main causes -must be attempted 2,3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic equipment technologic development has been providing new findings of ever smaller renal tumors in young individuals, therefore making way to needs of nephron sparing during surgical procedures towards removing such tumors; and partial nephrectomy relates to renal ischemia in order to allow nodule or renal mass removals; and, in order to prevent acute tubular necrosis, damage reduction due to blockage of renal blood flow -one of its main causes -must be attempted 2,3 .…”
Section: Discussionmentioning
confidence: 99%
“…The kidney has low tolerance to ischemia; human solitary kidneys afford no more than 20 minutes on cold ischemia and no more than 35 minutes on warm ischemia 3 . Ischemia reversibility hinges on three variables: histology after reperfusion, ATP regeneration capabilities, and the ability to keep intracellular calcium homeostasis 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Multivariate analysis in the present study supports the notion that ischemia time is an independent predictor of renal function after PN. 25 A recent study suggested that the amount of preserved parenchyma and its baseline functionality could be the primary determinants of ultimate renal function after PN, although type and duration of ischemia remain the most important factors. 11 Shortening ischemia time, cooling a kidney during the period of ischemia, and optimizing the amount of preserved parenchyma could be the most important factors in renal protection against ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…In view of studies demonstrating negligible effects on renal function after renal pedicle clamping for 90 minutes in porcine models [14][15][16] as well as retrospective clinical observations suggesting that WIT of 40 to 55 minutes may be tolerated, 16,17 some have asserted that the kidney can tolerate longer periods of WIT. Conversely, others have contended that the cutoff defining safe WIT be drawn at 20 minutes, [18][19][20] a view supported by a recent international collaborative review. 21 While efforts to define an appropriate cutoff for WIT abound, a compelling joint Cleveland Clinic/Mayo Clinic study examined the impact of WIT as a continuous variable on renal functional outcomes.…”
Section: Discussionmentioning
confidence: 99%